Indocyanine Green Fluorescence-Guided Surgery in Pediatric Hepatobiliary Procedures: A Feasibility Study for Improved Intraoperative Visualization - T.K, Jayakumar; Rathod, Kirtikumar Jagdish; Saxena, Rahul; Pathak, Manish; Jadhav, Avinash S.; Nayak, Shubhalaxmi; Varshney, Vaibhav; Soni, Subhash Chandra; Sinha, Arvind (European Journal of Pediatric Surgery, 2025)
Introduction Indocyanine green (ICG) fluorescence-guided surgery (FGS) is reported extensively in adult operations, but its safety and applications in pediatric populations remain to be comprehensively understood. The dose, administration protocols, and intraoperative imaging benefits in pediatric hepatobiliary operations are not clear.Objectives This study aimed to identify the feasibility and applications of ICG FGS in hepatobiliary surgeries (for biliary atresia, choledochal cyst, and cholelithiasis) in children.Methods This is a prospective observational study conducted from January 2021 to December 2022. A standard ICG dose of 0.5 mg/kg/dose was administered intravenously to children undergoing operations for biliary atresia (18–24 hours), choledochal cyst (12–18 hours), and cholelithiasis (2–6 hours) before the operation. Intraoperative imaging features and adverse events were recorded.Results ICG FGS was performed in 17 patients. In biliary atresia (n = 9), liver fluorescence varied in each case, the gallbladder did not show fluorescence, and there was increasing fluorescence as we reached the right depth during the excision of fibrous biliary remnants. In choledochal cyst (n = 6) operations and cholecystectomy (n = 2), real-time imaging provided anatomical details of the biliary tree and helped in safe dissection. No ICG-related adverse events occurred.Conclusion ICG FGS appears safe, feasible, and beneficial in pediatric hepatobiliary surgeries. For conditions like biliary atresia, choledochal cysts, and cholecystectomy, ICG facilitates safer surgical navigation and may reduce intraoperative complications. Future studies with standardized protocols and quantitative fluorescence assessment are needed to further refine its use and confirm its impact on surgical outcomes.
Keywords: indocyanine green; fluorescence-guided surgery; pediatric hepatobiliary surgery